2016
DOI: 10.1590/0103-8478cr20150253
|View full text |Cite
|
Sign up to set email alerts
|

Association of secondary traits with yield in maize F 1 's

Abstract: The objective was to identify phenotypic and genotypic associations, and cause-and-effect relations of secondary components on primary components to establish criteria in the indirect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…These differences may have occurred due to environmental effects embedded in the phenotypic trait associations (Ferreira et al., 2008). This finding has also been made in other studies involving the decomposition of correlations of different types (Baretta et al., 2016; Nardino, Souza, et al., 2016).…”
Section: Resultssupporting
confidence: 83%
“…These differences may have occurred due to environmental effects embedded in the phenotypic trait associations (Ferreira et al., 2008). This finding has also been made in other studies involving the decomposition of correlations of different types (Baretta et al., 2016; Nardino, Souza, et al., 2016).…”
Section: Resultssupporting
confidence: 83%
“…Thus, studies evaluating tassel traits related to grain yield have been carried out in half-sib families of an ESALQ-PB1 population (Andrade and Miranda Filho, 2008), in parental lines of Pioneer-brand maize hybrids (Lauer et al, 2012), in recombinant inbred lines in temperate and tropical climates (Brewbaker, 2015), in inbred lines of two heterotic groups (Nardino et al, 2016a), and in F1 hybrids (Nardino et al, 2016b). In general, those studies have confirmed the relationship between tassel traits and grain yield.…”
Section: Introductionmentioning
confidence: 95%
“…Evaluating grain yield components of maize hybrids grown in four different environments from southern Brazil, Nardino et al (2016) found no significant interaction. Paixão (2008) verified significant genotype × environment interaction for plant height and spike insertion height, evaluating genotypes of broad genetic basis.…”
Section: Resultsmentioning
confidence: 90%